Board structure, ownership concentration, and executive compensation in Chinese listed firms - Shan, Qi (2020)
This dissertation aims to examine the impact of board structure and ownership concentration on executive compensation in an emerging economic market, China. It also aims to offer the latest supplement on existing researches. By combining various perspectives of prior studies with Chinese market features as research background, this dissertation selects a sample of 912 non-financial firms listed at Shanghai and Shenzhen Stock Exchanges from 2015 to 2019. Based on these observations, this dissertation further develops a firm-fixed effect model and use descriptive analysis, correlation analysis, and regression analysis to test research hypotheses empirically. The empirical results indicate that board duality and ownership concentration are positively related to executive compensation, while board independence and board size are negatively correlated with executive compensation. The results all keep consistent with the views of agency theory and managerial power theory. These conclusions provide some new insights on the executive compensation researches; they also have some economic implications on Chinese government and firms to deal with the high executive compensation issue.